The European MultiPartner IPF registry (EMPIRE): validating long-term prognostic factors in idiopathic pulmonary fibrosis - Tran, Tanja; Šterclová, Martina; Mogulkoc, Nesrin; Lewandowska, Katarzyna; Müller, Veronika; Hájková, Marta; Kramer, Mordechai R; Jovanović, Dragana; Tekavec-Trkanjec, Jasna; Studnicka, Michael; Stoeva, Natalia; Hejduk, Karel; et al. (Respiratory research, 2020)
BACKGROUND: Several registries of idiopathic pulmonary fibrosis (IPF) have been established to better understand its natural history, though their size and duration of follow-up are limited. Here, we describe the large European MultiPartner IPF Registry (EMPIRE) and validate predictors of long-term survival in IPF. METHODS: The multinational prospective EMPIRE registry enrolled IPF patients from 48 sites in 10 Central and Eastern European countries since 2014. Survival from IPF diagnosis until death was estimated, accounting for left-truncation. The Cox proportional hazards regression model was used to estimate adjusted hazard ratios (HR) of death for prognostic factors, using restricted cubic splines to fit continuous factors. RESULTS: The cohort included 1620 patients (mean age at diagnosis 67.6 years, 71% male, 63% smoking history), including 75% enrolled within 6 months of diagnosis. Median survival was 4.5 years, with 45% surviving 5 years post-diagnosis. Compared with GAP stage I, mortality was higher with GAP stages II (HR 2.9; 95% CI: 2.3-3.7) and III (HR 4.0; 95% CI: 2.8-5.7) while, with redefined cut-offs, the corresponding HRs were 2.7 (95% CI: 1.8-4.0) and 5.8 (95% CI: 4.0-8.3) respectively. Mortality was higher with concurrent pulmonary hypertension (HR 2.0; 95% CI: 1.5-2.9) and lung cancer (HR 2.6; 95% CI: 1.3-4.9). CONCLUSIONS: EMPIRE, one of the largest long-term registries of patients with IPF, provides a more accurate confirmation of prognostic factors and co-morbidities on longer term five-year mortality. It also suggests that some fine-tuning of the indices for mortality may provide a more accurate long-term prognostic profile for these patients.
Keywords: Prospective Studies; Humans; následné studie; prospektivní studie; Europe; míra přežití; reprodukovatelnost výsledků; Comorbidity; Time Factors; Follow-Up Studies; Registries; komorbidita; mužské pohlaví; Survival Rate; Evropa; časové faktory; registrace; ženské pohlaví; idiopatická plicní fibróza; lidé; Reproducibility of Results; Idiopathic Pulmonary Fibrosis; Aged; senioři; Male; Female